Medical and cosmeceutical applications for enhancement of partial-thickness skin graft donor-site healing - Galip Gencay Ustun; Figen Ozgur; Sueda Hekimoglu (Turkish Journal of Plastic Surgery, 2020)
Introduction: After partial-thickness skin graft (PTSG) harvesting, a dermal surface is exposed and an iatrogenic wound is created. Application of various agents has been studied for enhancement of healing process in PTSG donor area. The ideal agent should accelerate healing, provide comfort to the patient, not allow infection, and be easily applicable and cheap. Materials and Methods: The Cochrane Central Register of Controlled Trials, PubMed, Scopus. and EMBASE databases were screened for words (“skin graft” + “donor”), by using time limits between 1989 and 2018. This study involved a total of 5 systematic reviews and 43 original articles which met the inclusion criteria. Articles were reviewed and parameters such as healing time, pain, infection rate, cosmetic result, and cost were extracted. Results: Systematic reviews favor moist dressing materials over dry ones considering healing time and patient comfort. Hydrocolloids provide rapid wound healing, and dressing changes do not cause any disruption to the newly regenerated epithelium. Alginates seem to have a longer healing time than hydrocolloid materials. Polyurethane films are characterized by rapid epithelialization and painless monitoring as well as low costs. The epithelialization time of MEBO®, a cosmeceutical product, is reported to be faster than polyurethane films. Local and systemic drug applications warrant further research before routine clinical usage. Conclusion: Dressing materials are the most commonly used and appropriate group according to the studies performed to date. It is seen that moist dressing materials are more favorable. Although there is not a subgroup with a clear superiority, it can be seen that the hydrofiber and polyurethane film groups are one step ahead in terms of ease of use, patient comfort, epithelialization speed, and scar quality. Polyurethane films have a cost advantage to the hydrofiber group.